Formulation and Evaluation of Oral Fast Dissolving Film - Nishant P Deshmukh; Dr. Nishant N. Bobade; Anuradha S. Khedkar; Mahendra A. Patil (Asian Journal of Pharmaceutical Research and Development, 2025)
The objective of present research work was to select cyclodextrins derivative for inclusion complex with Ezetimibe and formulate fast dissolving film to enhance pharmacokinetic and pharmacodynamic performance of drug.In this work, Hydroxypropyl Methylcellulose (HPMC) E5 and E15 were used as primary film-forming polymers in various combinations with pectin and glycerine as a plasticizer. The solvent casting method was employed to prepare the films. To improve the solubility and dissolution rate of Ezetimibe—a BCS Class II drug with low water solubility—inclusion complexes were developed using β-cyclodextrin, confirmed via FTIR, DSC, and XRD analyses. A 3² factorial design was implemented to systematically study the impact of formulation variables on key film characteristics such as disintegration time, drug content uniformity, folding endurance, and in vitro drug release. Among the formulations, batch F3 showed the most promising results, withRapid disintegration within 22 seconds, High drug content (98.87%), Superior tensile strength and folding endurance, Maximized drug release (above 95% within 5 minutes). The optimized batch followed first-order release kinetics, as validated by kinetic modelling (Higuchi, Korsmeyer-Peppas, and Hixson-Crowell models).Stability studies of batch F3 under accelerated conditions demonstrated excellent physicochemical stability for up to 3 months, confirming formulation robustness.The study concludes that Ezetimibe-loaded oral films developed using HPMC E5/E15, pectin, and glycerine can serve as a patient-friendly, fast-dissolving alternative dosage form with improved bioavailability and therapeutic efficacy, opening avenues for innovative drug delivery systems in lipid-lowering therapy.